2013
DOI: 10.3762/bjoc.9.235
|View full text |Cite
|
Sign up to set email alerts
|

Acid, silver, and solvent-free gold-catalyzed hydrophenoxylation of internal alkynes

Abstract: SummaryA range of arylgold compounds have been synthesized and investigated as single-component catalysts for the hydrophenoxylation of unactivated internal alkynes. Both carbene and phosphine-ligated compounds were screened as part of this work, and the most efficient catalysts contained either JohnPhos or IPr/SIPr. Phenols bearing either electron-withdrawing or electron-donating groups were efficiently added using these catalysts. No silver salts, acids, or solvents were needed for the catalysis, and either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Certain members of this family of organometallic complexes also exhibit interesting photophysical and biological properties, and therefore are extremely valuable materials . These compounds have also been used as substrates in cross‐coupling reactions, and have recently been shown as efficient pre‐catalysts in the acid‐ and silver‐free hydrophenoxylation of alkynes . Despite recent advances, their reactivity remains largely unexplored, presumably because of the methods used for their preparation, which can be viewed as operationally complex.…”
Section: Introductionmentioning
confidence: 99%
“…Certain members of this family of organometallic complexes also exhibit interesting photophysical and biological properties, and therefore are extremely valuable materials . These compounds have also been used as substrates in cross‐coupling reactions, and have recently been shown as efficient pre‐catalysts in the acid‐ and silver‐free hydrophenoxylation of alkynes . Despite recent advances, their reactivity remains largely unexplored, presumably because of the methods used for their preparation, which can be viewed as operationally complex.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the same research group found out that water is fundamental for such a reaction, except for studies with phenols and aryl alkynes. 11,56 Further, Nolan and Reek have recently confirmed the need for dual gold catalysis by encapsulation of the hydroxylated gold dimer. 54 Scheme 1.…”
Section: Introductionmentioning
confidence: 98%
“…The barrier for this transition state is 7.2 kcal/mol higher in energy with respect to the barrier that leads to the trans-product; the corresponding structures of IV differ in energy by 2.7 kcal/mol, with the structure on the trans-pathway being lower in energy, as previously reported yet. 56 Next, the reaction pathway for the simplified catalyst [Au(IMe)] + -where the 2,6-di(isopropyl)phenyl substituents on the NHC are substituted by methyl groups -was calculated ( Figure 2). Furthermore, first in Figure 2a the diphenylacetylene was replaced with but-2-yne for the sake of simplicity.…”
Section: Digold Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…We continue to be interested in the development of highly efficient and environmentally benign catalytic methodologies for the synthesis of organic molecules; therefore, we sought to combine the advantages offered by an eco-friendly solvent-free protocol, and the atom-and step-economy of sequential strategies. We envisioned that if we could adapt our hydrophenoxylation protocol to solvent-free conditions, [7] to then apply cross-coupling strategies on the resulting product, in a sequential manner, this would permit access to more complex organic entities in an easily conducted diversity-oriented manner.…”
mentioning
confidence: 99%